AUDIT DAN PENGEMBANGAN BAHAN AJAR EFEKTIF BERBASIS ANALISIS KEBUTUHAN DI SD DI SDN 184 DARE AJUE KABUPATEN SOPPENG - Anisa Waliyyu Rusman; Suardi (STKIP Subang, 2026)
Limited variation of instructional materials and the underutilization of learning media in the implementation of the Merdeka Curriculum in elementary schools may affect students’ engagement, motivation, and learning outcomes. This study aims to audit existing instructional materials, analyze learning needs, and develop more effective and contextual materials at SDN 184 Dare Ajue, Soppeng Regency. A descriptive qualitative approach was employed through instructional material audits, classroom observations, interviews with school principals and teachers, and student group discussions. The data were analyzed to examine the alignment of instructional materials with the principles of the Merdeka Curriculum and students’ learning needs. The results indicate that instructional materials are still dominated by printed resources, while the use of digital materials remains limited due to facility constraints. The needs analysis reveals that students prefer visual, contextual, and activity-based learning materials. Based on these findings, a thematic student worksheet was developed emphasizing observation, discussion, and reflection activities. The implementation shows increased student participation, engagement, and learning motivation. These findings highlight the importance of needs-based auditing in producing relevant and effective instructional materials.